ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI MINAT BELAJAR PESERTA DIDIK PADA KELAS VIII MATERI RELASI DAN FUNGSI - Fajriani, Kurnia; Suharti, Suharti; Abrar, Andi Ika Prasasti; Kusumayanti, Andi (Al Asma: Journal of Islamic Education, 2025)
Mathematical communication skills in Indonesia are categorized as low. Low mathematical communication skills are caused by students' lack of interest in learning mathematics. In addition, relations and functions are other factors that can affect students' mathematical communication skills. This study aims to determine the mathematical communication skills of students in grade VIII who have high, medium, and low learning interests and to find out what obstacles cause low mathematical communication skills of students in grade VIII on the material of relations and functions. This type of research is qualitative descriptive research. The subjects of this study were students of class VIII A of SMP Negeri 3 Sinjai. From these subjects, 3 students were selected, consisting of 1 student with a high learning interest category, 1 student with a medium learning interest category, and 1 student with a low learning interest category. The main instrument used in this study was the researcher himself. The data collection techniques used were learning interest questionnaires, mathematical communication ability tests, and interviews. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study showed that students with a high category were able to master 3 indicators, and students with a medium learning interest category were able to master 2 indicators, while students with mathematical communication skills in the low learning interest category were able to master 1 indicator. The obstacles that cause low mathematical communication skills of students consist of namely that high learning interest significantly influences students' mathematical communication skills. Therefore, efforts need to be made to increase students' learning interest to develop their mathematical communication skills well.